The interrelationship between food security, climate change, and gender-based violence: A scoping review with system dynamics modeling. - Pooja Agrawal; Lori Ann Post; Janis Glover; Denise Hersey; Piya Oberoi; Brian Biroscak (PLOS Global Public Health)
Gender-based violence (GBV) is a global public health and human rights problem that is exacerbated by social and environmental stressors for a multitude of interpersonal, cultural, and economic reasons. Through sudden disruptions in the microclimate of a region, climate shocks often have a negative impact on food security, which correlates with increases in GBV. Associations between the various combinations of GBV, climate change, and food insecurity have been documented in the growing international literature, but questions remain about these associations that require further clarification. The impact of the COVID-19 pandemic caused by SARS-CoV-2 provides insight through a real time demonstration into these interactions. This review of the global literature examines the interplay between GBV, climate change, and food insecurity-including recent literature regarding the COVID-19 pandemic. This review covers original research studies employing both quantitative and qualitative methodology, those that conducted secondary analyses of existing data sources and perspective pieces derived from observed evidence. An additional analytic layer of system dynamics modeling allowed for the integration of findings from the scoping review and discovery of additional insights into the interplay between disasters, food insecurity, and GBV. Findings from this review suggest that the development and adaptation of evidence-based, focused interventions and policies to reduce the effects of climate shocks and bolster food security may ultimately decrease GBV prevalence and impact.